Moderate deviation principle for the 2D stochastic convective Brinkman–Forchheimer equations. Issue 7 (3rd October 2021) - Mohan, Manil T.
ABSTRACT: This work is concerned about some asymptotic behaviour of the two-dimensional stochastic convective Brinkman–Forchheimer (SCBF) equations, which describes the motion of incompressible viscous fluid through a rigid, homogeneous, isotropic, porous medium. We establish a central limit theorem and a moderate deviation principle for the SCBF equations using a variational method (based on weak convergence approach) developed by Budhiraja and Dupuis.